Tell me I'm worthless - Rumfitt, Alison (A Nightfire Book, published by Tom Doherty Associates, 2023)
"Alison Rumfitt's Tell Me I'm Worthless is a dark, unflinching haunted house story that confronts both supernatural and real-world horrors through the lens of the modern-day trans experience. "Ambitious, brutal, and brilliant." -Gretchen Felker-Martin, author of Manhunt Three years ago, Alice spent one night in an abandoned house with her friends, Ila and Hannah. Since then, Alice's life has spiraled. She lives a haunted existence, selling videos of herself for money, going to parties she hates, drinking herself to sleep. Memories of that night torment Alice, but when Ila asks her to return to the House, to go past the KEEP OUT sign and over the sick earth where teenagers dare each other to venture, Alice knows she must go. Together, Alice and Ila must face the horrors that happened there, must pull themselves apart from the inside out, put their differences aside, and try to rescue Hannah, whom the House has chosen to make its own. Cutting, disruptive, and darkly funny, Tell Me I'm Worthless is a vital work of trans fiction that examines the devastating effects of trauma and the way fascism makes us destroy ourselves and each other"--